Perilaku Kepemimpinan Kepala Sekolah Berbasis Nilai-Nilai Siriâ - Waqib, Abdul (Program Studi Administrsi Pendidikan Program Pascasarjana UNM, 2013)
The study aims at examining the empirical descriptions of reason, process, andÂ the impact of the application of Siri values on the principalâsââ leadership behavior at SMAN 2 Pangkajene in Pangkep district. The location of the study was centered at SMAN 2 Pangkajene in Pangkep district. The type of the study used inÂ this study was descriptive qualitative. The main source of the data was the principal which also involved the vice-principal, the head of administration, and teachers as other informants. Data were collected through observation, guided interview, and documentation. The data then were analyzed using qualitative method conducted in several stages, namely data reduction, data presentation, data validity. The results of the study reveal that the application of ââSiriâ values on the principalâs leadership behavior at SMAN 2 Pangkajene in Pangkep district viewed from (1) the reasons of application due to a) bureaucratic expectation to make itÂ into realization, b) norms and informal values which internalized within oneself as part of life experience, c) the needs and individual motive to be fulfilled, and d) organizational objective to be achieved. (2) the process of application consisted of the process of a) task oriented leadership behavior, b) relationship oriented leadership behaviors, and c) change orientation leadership behavior; (3) the impact of application the impact toward a) the school as the education institution and b) the employees of the institution as education implementer such as the principal, teacher and staff, and students. Key words: Siri values andÂ principalâsââ leadership behavior.